Determinan Produktivitas Tenaga Kerja di Indonesia - Muhammad Maulana (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2023)
Over the past 31 years, labor productivity in Indonesia has tended to decline. This decreased productivity needs attention. This study aims to examine the determinants of labor productivity in Indonesia by using indicators of capital deepening, human capital, technology, macroeconomic conditions, trade openness, and wages. Using time series data for the period 1990-2021, the model is estimated using the fully modified least squares (FMOLS) technique. The results obtained indicate that human resources are the largest determinant of labor productivity among other factors. Technology does not significantly affect labor productivity. Meanwhile, trade openness and wages negatively affect labor productivity. This research shows that policy makers need to boost digital infrastructure development in order to optimally utilize technology, increase public awareness to use more domestic products, and support pro-business policies in determining labor wages.